Does Gold Act as a Hedge or a Safe Haven? Evidence from Pakistan (The Pakistan Development Review, 2020)
This paper seeks to determine whether in Pakistan gold protects investors against the risks associated with the exchange rate, oil shocks, and stock returns by testing the hedging and safe haven properties of gold returns for the period from August 1997 to May 2016. The analysis has been done to understand the relationship between moderate (normal) and extremely tumultuous conditions through least squares and DCC-GARCH models. The key results indicate that gold acts as a hedge against exchange rate risk only whereas it acts as a safe haven in terms of the risks associated with the oil, exchange rate and stock market shocks—thereby indicating that investors can potentially invest in gold to hedge against losses emanating from the exchange rate, while they may avoid potential losses originating from turmoil conditions in terms of the exchange rate, oil, and stock markets. JEL Classification: E32, F31. Keywords: Gold Returns, Safe Haven, Hedge, DCC GARCH